I BELIEVE IN THE HOLY EARTHY CHURCH: TOWARD AN ECOLOGICAL REINTERPRETATION OF THE HOLINESS OF THE CHURCH - David N. Field (Scriptura, 2013)
This article develops a re-interpretation of the holiness of the church. It comprises two main sections. The first re-examines the motif of holiness by critically examining use of this motif in selected biblical traditions. This will form the basis for the development of an ecological understanding of holiness. The second part will examine what on earth it means to confess that the church is ecologically holy given, its all too obvious failures and the pervasive influence of the socio-cultural and politico-economic forces that are destructive to the earth.   doi: 10.7833/111-1-20